2021
DOI: 10.4218/etrij.2020-0147
|View full text |Cite
|
Sign up to set email alerts
|

Trust‐aware secure routing protocol for wireless sensor networks

Abstract: A trust‐aware secure routing protocol (TSRP) for wireless sensor networks is proposed in this paper to defend against varieties of attacks. First, each node calculates the comprehensive trust values of its neighbors based on direct trust value, indirect trust value, volatilization factor, and residual energy to defend against black hole, selective forwarding, wormhole, hello flood, and sinkhole attacks. Second, any source node that needs to send data forwards a routing request packet to its neighbors in multi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Hu et al, 27 have suggested a trust‐aware protected routing protocol for protecting against the interior attack. Initially, every path computes the complete faith values of its neighbors due to straight trust value, unintended trust value, and remaining energy.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al, 27 have suggested a trust‐aware protected routing protocol for protecting against the interior attack. Initially, every path computes the complete faith values of its neighbors due to straight trust value, unintended trust value, and remaining energy.…”
Section: Literature Surveymentioning
confidence: 99%
“…There are several CH selection methods, 16,22,[24][25][26][27][28][29] that methods have several limitations, such as increasing delay, poor network lifetime, and low throughput and do not provide efficient CH selection. But, this proposed work overcomes all these issues and provides efficient CH selection with high throughput.…”
Section: Problem Statementmentioning
confidence: 99%
“…In order to resist attacks such as black hole and selective forwarding, Ref. [ 36 ] proposes a trust aware secure routing protocol to resist these attacks, in which each node calculates the comprehensive trust value of its neighbors based on the direct trust, the indirect trust, the volatility factor, and the residual energy. Reference [ 37 ] proposes an atomic search sunflower optimization method to provide trust based routing.…”
Section: Common Applications Of Trustmentioning
confidence: 99%
“…Hu et al [16] provided security against the attacks by developing a Trust-aware Secure Routing Protocol (TSRP). Here, the node's trust value was calculated using the residual energy, volatilization factor, direct trust value and indirect trust value.…”
Section: Related Workmentioning
confidence: 99%